A Monte Carlo study of early gas expulsion and evolution of star clusters: new simulations with the MOCCA code in the amuse framework. Issue 4 (17th June 2022) - Leveque, A; Giersz, M; Banerjee, S; Vesperini, E; Hong, J; Portegies Zwart, S
ABSTRACT: We introduce a new prescription for the evolution of globular clusters (GCs) during the initial embedded gas phase into a Monte Carlo method. With a simplified version of the Monte Carlo MOCCA code embedded in the amuse framework, we study the survival of GCs after the removal of primordial gas. We first test our code and show that our results for the evolution of mass and Lagrangian radii are in good agreement with those obtained with N-body simulations. The Monte Carlo code enables a more rapid exploration of the evolution of systems with a larger number of stars than N-body simulations. We have carried out a new survey of simulations to explore the evolution of globular clusters with up to N = 500 000 stars for a range of different star formation efficiencies and half-mass radii. Our study shows the range of initial conditions leading to the clusters' dissolution and those for which the clusters can survive this early evolutionary phase.